THE LEGAL NATURE OF THE ADMINISTRATIVE REAL ACT - Nugzar Putkaradze; Murman Gorgoshadze (International Journal of Innovative Technologies in Social Science, 2026)
This article examines the administrative real act as a distinct legal form of public administration and analyses its doctrinal foundations, characteristics, typology, and criteria of differentiation from the administrative act, internal administrative measures, and administrative silence. The study demonstrates that, although the administrative real act lacks a regulatory nature, it may produce substantial legal consequences, including interference with fundamental rights. Consequently, its legal qualification cannot depend solely on formal criteria but must be based on a result-oriented analysis.Drawing upon German administrative law doctrine and Georgian legislative and judicial practice, the article substantiates the admissibility of judicial review of real acts whenever factual conduct affects the individual’s legal sphere. Particular attention is devoted to the development of judicial standards, including competence, legitimacy of purpose, proportionality, intensity of interference, and reversibility of consequences. The research highlights the growing importance of a result-oriented approach in ensuring effective legal protection and preventing administrative arbitrariness.The article concludes that clearer normative regulation, consolidation of judicial practice, and strengthened doctrinal engagement are necessary to ensure the coherent application of the administrative real act within a rule-of-law framework.